On-Farm Evaluation in Uganda of Iron Concentration and Iron Bioavailability in the Fast Cooking Manteca Yellow Bean (Phaseolus vulgaris L.). (29th May 2020) - Glahn, Raymond; Cichy, Karen; Wiesinger, Jason
Abstract: Objectives: To evaluate the genotype by environment (GxE) influence on Fe concentration and Fe bioavailability of select fast cooking bean varieties in Uganda. Methods: This study compared two fast cooking Manteca genotypes (Ervilha, Cebo) to eight other white, yellow and red mottled genotypes, which included farmer local check varieties NABE15 and Masindi yellow. Genotypes were produced as a group across nine on-farm locations in Uganda over two field seasons. Cooking time was standardized with a Mattson cooking device and iron bioavailability was measured with a Caco-2 bioassay, which measures ferritin formation (ng ferritin/mg cell protein) relative to a navy bean reference control (cv. Merlin) as an indicator of iron uptake. Iron concentration was measured via inductively coupled plasma emission spectroscopy (ICP-ES). Results: Iron concentrations of the cooked beans were highly variable across Uganda with low board sense heritability (plot basis 0.40). Iron concentrations in cooked seed ranged from 41 to 97 mg/g, with a mean of 67 mg/g across the nine production environments. Iron bioavailability ranged from 8 to 116% of navy bean control and was highly heritable (plot basis 0.80) among this subset of white, yellow and red beans. The fast cooking white (Blanco Fanesquero) and two Manteca yellow beans consistently had the highest iron bioavailability (64 – 116% of control) across all locations in Uganda. There was a significant negative association (r = −0.438, p  ≤ 0.05) between cooking time and iron bioavailability of the white, yellow and red beans produced in Uganda. Conclusions: This study demonstrates the high iron bioavailability trait of the two fast cooking Manteca yellow beans are stable across different production environments in Uganda. This study presents evidence that breeding for fast cooking times in yellow beans is not only a valuable end-use quality trait beneficial to smallholder farmers in Uganda, but could also be a sustainable approach for delivering more bioavailable iron to consumers in East Africa. The high variability of Fe concentration within genotypes raises concern that high Fe concentration can be a sustainable trait in Uganda. Funding Sources: U.S. Agency for International Development (USAID), U.S. Department of Agriculture (USDA).